The Psychology of Risk Influence and Investor Sentiment on Investment Decision Making in the Indonesian Stock Market - Sinaga, Muhammad Apri Wirawan; Nuzula, Nila Firdausi; Damayanti, Cacik Rut (Jurnal Ilmiah Akuntansi dan Bisnis, 2023)
This study aims to provide empirical evidence concerning the influence of risk psychology and investor sentiment on investment decision-making. The focus of this research is individual investors in Malang, who participate in the Indonesian stock market. Data collection was conducted from December 2022 to February 2023, utilizing a proportionate stratified random sampling method. The sample size meeting the specified criteria was 100 respondents, whose data was subsequently analyzed using variance-based structural equation modeling, commonly referred to as SEM-PLS. The findings suggest that risk psychology has a positive, albeit insignificant, effect on investment decision-making. However, risk psychology significantly influences investor sentiment, which in turn has a substantial and positive effect on investment decision-making. The study also provides empirical evidence of a robust indirect effect of risk psychology on investment decision-making. Keywords: psychology of risk, investor sentiment, investment decision